No Effect of Dietary Fish Oil Supplementation on the Recruitment of Brown and Brite Adipocytes in Mice or Humans under Thermoneutral Conditions. Issue 2 (21st December 2020) - Maurer, Stefanie F.; Dieckmann, Sebastian; Lund, Jens; Fromme, Tobias; Hess, Anne Lundby; Colson, Cécilia; Kjølbæk, Louise; Astrup, Arne; Gillum, Matthew Paul; Larsen, Lesli Hingstrup; Liebisch, Gerhard; Amri, Ez‐Zoubir; et al.
Abstract : Scope: Brown and brite adipocytes within the mammalian adipose organ provide non‐shivering thermogenesis and thus, have an exceptional capacity to dissipate chemical energy as heat. Polyunsaturated fatty acids (PUFA) of the n3‐series, abundant in fish oil, have been repeatedly demonstrated to enhance the recruitment of thermogenic capacity in these cells, consequently affecting body adiposity and glucose tolerance. These effects are scrutinized in mice housed in a thermoneutral environment and in a human dietary intervention trial. Methods and results: Mice are housed in a thermoneutral environment eliminating the superimposing effect of mild cold‐exposure on thermogenic adipocyte recruitment. Dietary fish oil supplementation in two different inbred mouse strains neither affects body mass trajectory nor enhances the recruitment of brown and brite adipocytes, both in the presence and absence of a β3‐adrenoreceptor agonist imitating the effect of cold‐exposure on adipocytes. In line with these findings, dietary fish oil supplementation of persons with overweight or obesity fails to recruit thermogenic adipocytes in subcutaneous adipose tissue. Conclusion: Thus, the authors' data question the hypothesized potential of n3‐PUFA as modulators of adipocyte‐based thermogenesis and energy balance regulation. Abstract : Fish oil supplementation has been repeatedly demonstrated to enhance the recruitment of thermogenic brite cells in subcutaneous adipose tissue. These cells, expressing the uncoupling protein 1 (UCP1), have an exceptional capacity to dissipate chemical energy as heat and are proposed reduce body adiposity by affecting energy balance. In this study, dietary supplementation of fish oil in mice housed at 30°C and humans did not affect the recruitment of UCP1 expressing brite adipocytes.